Couple Satisfaction and Dark Triad Personality Traits: An Empirical Study - Popa, Brigitte (New Trends in Psychology, 2025)
This study examines the relationship between couple satisfaction and the Dark Triad personality traits—narcissism, Machiavellianism, and psychopathy—while also exploring gender differences in both relational satisfaction and the expression of these traits. Previous research has shown that personality traits shape relationship outcomes, with the Dark Triad increasingly recognized as a cluster of socially aversive traits that may undermine intimacy. Yet, findings remain inconsistent, particularly regarding cultural and gender-related variations. A quantitative design was applied using standardized instruments: the Short Dark Triad questionnaire (SD3) (Jones & Paulhus, 2014) and the Dyadic Adjustment Scale (DAS-32) (Spanier, 1976). Statistical analyses were conducted with SPSS. Results indicated no significant correlations between Dark Triad traits and overall couple satisfaction, contrary to expectations. However, gender differences emerged: men scored higher on psychopathy and Machiavellianism, while women reported greater satisfaction. These findings suggest that the influence of dark personality traits on relationships is more complex than assumed and may be moderated by cultural or relational factors. The study contributes to a nuanced understanding of couple dynamics and offers insights relevant for counseling and therapeutic practice.